Effectiveness of Acupressure Therapy in Reducing Blood Pressure Among Older Adults with Hypertension - Hartati, Sri; Kamesworo; Elviani, Yeni (Lembaga Chakra Brahmanda Lentera (Chakra Brahmanda Lentera Institute) [CANDLE], 2025)
Background: Hypertension is a non-communicable disease that remains one of the leading causes of premature death worldwide. However, in the elderly population, there is a decline in muscle mass and strength, decreased heart rate, reduced exercise tolerance, and lowered cardiovascular capacity. The objective of this study was to determine the effect of acupressure therapy on blood pressure reduction in elderly patients with hypertension Methods: This study employed a quantitative research design using a quasi-experimental method to evaluate the effectiveness of the intervention. The research was conducted among elderly individuals with hypertension in the working area of Pagar Agung Public Health Center, Lahat, in 2023 Result: The results of the paired t-test showed a statistically significant difference in blood pressure before and after acupressure therapy, with a p-value of < 0.001 (p < 0.05). This indicates that acupressure therapy had a significant effect on reducing blood pressure in elderly patients with hypertension Conclusion: Acupressure therapy is effective in lowering blood pressure among older adults with hypertension. This non-pharmacological intervention can be considered as an alternative or complementary approach in hypertension management for the elderly population.